The Effects of Deep Brain Stimulation on Balance in Parkinson’s Disease as Measured Using Posturography—A Narrative Review - Bradley Lonergan; Barry M. Seemungal; Matteo Ciocca; Yen F. Tai (Brain Sciences)
Background: Postural imbalance with falls affects 80% of patients with Parkinson’s disease (PD) at 10 years. Standard PD therapies (e.g., levodopa and/or deep brain stimulation—DBS) are poor at improving postural imbalance. Additionally, the mechanistic complexity of interpreting postural control is a major barrier to improving our understanding of treatment effects. In this paper, we review the effects of DBS on balance as measured using posturography. We also critically appraise the quantitative measures and analyses used in these studies. Methods: A literature search was performed independently by 2 researchers using the PUBMED database. Thirty-eight studies are included in this review, with DBS at the subthalamic nucleus (STN-) (n = 25), globus pallidus internus (GPi-) (n = 6), ventral intermediate nucleus (VIM)/thalamus (n = 2), and pedunculopontine nucleus (PPN) (n = 5). Results: STN- and GPi-DBS reduce static sway in PD and mitigate the increased sway from levodopa. STN-DBS impairs automatic responses to perturbations, whilst GPi-DBS has a more neutral effect. STN-DBS may promote protective strategies following external perturbations but does not improve adaptation. The evidence regarding the effects on gait initiation is less clear. Insufficient evidence exists to make conclusions regarding VIM- and PPN-DBS. Conclusions: STN- and GPi-DBS have differing effects on posturography, which suggests site-specific and possibly non-dopaminergic mechanisms. Posturography tests should be utilised to answer specific questions regarding the mechanisms of and effects on postural control following DBS. We recommend standardising posturography measures and test conditions by expert consensus and greater long-term data collection, utilising ongoing DBS registries.